2020
DOI: 10.1213/ane.0000000000004494
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fluid Responsiveness in Prone Neurosurgical Patients Undergoing Protective Ventilation: Role of Dynamic Indices, Tidal Volume Challenge, and End-Expiratory Occlusion Test

Abstract: BACKGROUND: In patients in the prone position, the reliability of pulse pressure variation and stroke volume variation (PPV and SVV) and the use of functional hemodynamic tests to predict fluid responsiveness have not previously been established. Perioperatively, in this setting, optimizing fluid management can be challenging, and fluid overload is associated with both intraoperative and postoperative complications. We designed this study to assess the sensitivity and specificity of baseline PPV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 38 publications
1
33
1
Order By: Relevance
“…Moreover, the AUCs of PPV 8 and SVV 8 are also lower than those in studies conducted in patients ventilated with the VCV mode. Nevertheless, it has been showed that the AUCs of ΔPPV 6 − 8 and ΔSVV 6 − 8 in this study were not signi cantly different with those in previous studies [26][27][28]. Simultaneously, the correlation between the ΔPPV 6 − 8 and ΔSVV 6 − 8 after the TVC application and ΔCI after FC administration ( Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, the AUCs of PPV 8 and SVV 8 are also lower than those in studies conducted in patients ventilated with the VCV mode. Nevertheless, it has been showed that the AUCs of ΔPPV 6 − 8 and ΔSVV 6 − 8 in this study were not signi cantly different with those in previous studies [26][27][28]. Simultaneously, the correlation between the ΔPPV 6 − 8 and ΔSVV 6 − 8 after the TVC application and ΔCI after FC administration ( Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…Myatra et al [25] showed that the absolute changes in PPV and SVV induced by a tidal volume challenge were good predictors of fluid responsiveness, with AUCs of 0.99 and 0.97, respectively (threshold, PPV: 3.5%, SVV: 2.5%). In another recent study [26], the absolute changes in PPV and SVV after a tidal volume challenge showed acceptable predictabilities for fluid responsiveness, with high sensitivity and specificity even with patients in the prone position. Although the tidal volume challenge cannot be used in patients with spontaneous breathing, open-chest conditioning, or arrhythmia, this intervention can be a useful method to assess fluid responsiveness in the perioperative period under other circumstances.…”
Section: Tidal Volume Challengementioning
confidence: 87%
“…The study also found that during the increase in VT, if the absolute value of PPV increases by ≥3.5%, the fluid responsiveness can be predicted quite accurately (AUROC curve, 0.99) ( 30 ). Messina et al ( 31 ) conducted a tidal volume challenge (TVC) in the prone position patients, that is, increasing the tidal volume from 6 to 8 ml/kg in a short period of time, and attempting to use pulse pressure variability and stroke volume variability to assess the fluid responsiveness of a patient. In addition, the studies have pointed out that when the PPV of a patient is >13%, the passive leg raising tests are performed.…”
Section: Limitations Of Ppvmentioning
confidence: 99%